2021
DOI: 10.33448/rsd-v10i8.17109
|View full text |Cite
|
Sign up to set email alerts
|

Composição química, atividade bactericida e antioxidante dos óleos essenciais das folhas de Ocimum basilicum e Ocimum gratissimum (Lamiaceae)

Abstract: O gênero Ocimum da família Lamiaceae compreende um grupo de plantas bem conhecidas como Ocimum gratissimum L. (alfavaca) e Ocimum basilicum (manjericão). Estudos revelam que essas plantas apresentam atividade antimicrobiana, inseticida, antioxidante, antifúngica, analgésica e imunoestimulante. Neste contexto, o objetivo deste estudo foi analisar a composição química dos óleos essenciais de O. gratissimum e O. basilicum coletadas em diferentes horários e com diferentes tempos de extração, bem como, avaliar sua … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Antimicrobial, insecticidal, antioxidant, antifungal, analgesic, and immunostimulant potentials have also been observed in studies conducted with the species Ocimum gratissimum L. (alfavaca) and Ocimum basilicum (basil) (Vasconcelos et al, 2021).…”
Section: Bioactivity Of Essential Oilsmentioning
confidence: 78%
See 2 more Smart Citations
“…Antimicrobial, insecticidal, antioxidant, antifungal, analgesic, and immunostimulant potentials have also been observed in studies conducted with the species Ocimum gratissimum L. (alfavaca) and Ocimum basilicum (basil) (Vasconcelos et al, 2021).…”
Section: Bioactivity Of Essential Oilsmentioning
confidence: 78%
“…In this sense, the study by Vasconcelos et al (2021) showed that essential oils of O. gratissimum and O. basilicum showed good antioxidant activity in the sequestration of the DPPH free radical and bactericidal activity against strains of E. coli and S. aureus, with the essential oil of O. gratissimum showing greater inhibitory potential than the essential oil of O. basilicum, at the concentrations evaluated.…”
Section: Bioactivity Of Essential Oilsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is used as a condiment in cooking and as a sedative and anxiolytic, and in traditional medicines for headache and abdominal pain, cough, cold, and bronchitis (Silva et al, 2015a;Ashokkumar et al, 2020). Its essential oil has been used as an anesthetic (Silva et al, 2012;Silva et al, 2015a), antinociceptive (Rabelo et al, 2003;Sahouo et al, 2003;Paula-Freire et al, 2013), anti-inflammatory (Sahouo et al, 2003), antioxidant (Pereira and Maia, 2007;Vasconcelos et al, 2021), insecticide (Nguemtchouin et al, 2013), and antimicrobial against bacteria and fungi (Vasconcelos et al, 2021;Franco et al, 2007;Matasyoh et al, 2007;Adjou et al, 2013;Dambolena et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of O. gratissimum (EOGT) is composed of eugenol as a major constituent (Ashokkumar et al, 2020;Vasconcelos et al, 2021;Matasyoh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%